Characterisation of T cell responses during Staphylococcus aureus infection - Murphy, Alison (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2014)
The development of anti-S. aureus vaccines has consistently failed in clinical trials, likely due to inefficient induction of cellular immunity. A comprehensive understanding of the discrete T cell subsets critical for site-specific bacterial clearance will be necessary to inform the development of vaccines that efficiently target adaptive cellular immunity. To investigate how exposure to S. aureus impacts cellular immunity, a novel murine model of recurrent S. aureus peritonitis was developed. Prior exposure to S. aureus protected against subsequent infection through increased IFNγ production by CD4 and CD8 T cells, elevated IL-17 secretion by γδ T cells and enhanced phagocyte recruitment and activation.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin